IMPLEMENTATION OF HEALTHY AND CLEAN LIFESTYLES (PHBS) THROUGH THE ERGONOMIC HANDS WASHER AND SANITIZER - Dheasy Herawati; Nurul Aziza; Setyawan Setyawan (Universitas Ahmad Dahlan, 2021)
As a form of community service during this current Covid-19 pandemic, Universitas Maarif Hasyim Latif appointed several UMAHA Task Forces in collaboration with NU MWC Task Forces in Sidoarjo area as a form of concern to participate in the Clean and Healthy Lifestyle (PHBS) movement by providing counseling and assistance with ergonomic handwashing tools. This handwashing tool is designed without touching the water faucet and soap holder as a medium that is suspected of spreading the virus. As the result, the counseling and distributing pamphlets affected on the residents' understanding towards PHBS of around 46.7%. At the same time, user satisfaction with the ease of the tool is 46.2%. Simultaneous counseling needs to be done to slowly change the local community ways of thinking and behavior. While in terms of design, hand washing equipment still requires to be developed more with the addition of sensors.